Benefits of Community Involvement at the School Level - Dwyer, Stuart (The Australian Journal of Indigenous Education, 2002)
I would like to begin by providing a context that can be used to place my discussion about experiences at a remote school in the Northern Territory (NT) into perspective. In the NT 53% of schools are located in remote areas and these cater for up to 23% of NT students (Combe, 2000). The NT has the highest proportion of Indigenous students enrolled in schools with 35.2% of the overall student population identifying as Indigenous Australian (Collins, 1999). The next closest state is Western Australia with an Indigenous student enrollment average of 5.1 %, this is compared with a national average of 3.2%.